School Financing Strategies in Quality Improvement (Case Study at Sambas 2 State Junior High School) - Titis Wandrianto; Aswandi Aswandi; Wahyudi Wahyudi (STKIP Singkawang, 2019)
Financing education in schools is an important thing in effort to improve the quality of education. This study aims to (1) Planning financing strategies in improving school quality; (2) Implementation of financing strategies in improving school quality; and (3) Evaluation of financing strategies in improving school quality. The research approach used is qualitative research with a type of case study research. Data obtained through observation, interviews, and documentation in obtaining data. The stages carried out in the research are the stages of preparation, implementation, and reporting. Data were analyzed by analyzing data, compiling data, synthesizing, looking for patterns, finding out what was meaningful, what was researched and decided to be reported systematically. The results obtained from this study are (1) Planning strategies for improving the quality of Sambas 2 State Junior High School compiled and outlined in the form of RKS and RAPBS; (2) Implementation of financing strategies in Sambas 2 State Junior High School using economic unit strategies, donations of school committee funds and parents of students, submitting proposals to the government and school committees and BOS; (3) Evaluation of financing strategies in improving the quality of education in Sambas 2 State Junior High School is carried out through four stages: evaluation of results of activities for a year/semester and/or quarterly, evaluation of employee performance results through programs, evaluation carried out in accordance with organizational mechanisms, and evaluation analysis SWOT includes the results of internal and external analysis; (4) Evaluation of financing strategies at Sambas 2 State Junior High School is done by making school financial reports which are divided into several items according to the technical reporting guidelines. Based on the results of the study stating that the implementation of the quality improvement strategy through financing strategies at Sambas 2 State Junior High School has been running very well and is in accordance with the principles of financial management and the process of improving the quality of the institution.